The Role of Social Media Algorithms in Shaping Consumer Culture in the Digital Economy - Elvira Fitriyanti; Nabilaa Faizatuz Zuhriyah (Jurnal Ekonomi, Teknologi dan Bisnis, 2025)
The development of digital technology has made social media algorithms a dominant factor in shaping people's consumption behavior. This research aims to analyze the role of social media algorithms in creating consumer culture in Indonesia's digital economy era. Using a qualitative approach and an exploratory case study design, the study involved 18 participants consisting of active consumers, digital business actors, and digital culture experts. Data were collected through in-depth interviews, digital observation, and documentation, then analyzed using the Miles & Huberman interactive model through data reduction, data presentation, and conclusion drawing. The results show that social media algorithms influence consumer culture through three main mechanisms: personalized recommendation, viral loop effect, and cultural embedding. The majority of respondents admitted to trusting algorithmic recommendations more than manual searches, even encouraging more impulsive consumption behavior. Interviews with business actors revealed that algorithms accelerate trend cycles, create digital product hierarchies, and build consumer dependency. This research confirms that algorithms are not merely technical instruments but also cultural actors that shape consumption patterns and social identities. These findings have implications for digital business strategies, consumer literacy, and the formulation of consumer protection policies in the digital economy era.